Marginal cost of risk-based capital and risk-taking - CHEN, Tao (Institutional Knowledge at Singapore Management University, 2019)
We explore the impact of capital adequacy requirements on financial institutions' risk-taking behavior from a novel perspective. Specifically, we show that an important feature of the risk-based capital (RBC) system a built-in diversification benefit in aggregating risk categories induces moral hazard. We find that insurers that face lower marginal RBC costs of fixed-income (FI) investment tend to purchase riskier Fl securities. This relationship holds even when lower marginal RBC costs result from increased risk in other risk categories, which is an unintended consequence of the RBC's square root rule. Using Hurricanes Katrina and Sandy as exogenous shocks to the RBC cost, we find that insurers that suffered more in the two disasters undertook more risk in their Fl investments and witnessed an increase in their overall risk. We further show that insurers with a high RBC cost sell similar risky bonds during the financial crisis, presenting a source of systemic risk. These results provide an important regulatory implication for minimum capital calculation in capital regulation regimes.